Analytical Study of the Character And Thoughts of Mashaikh Mujaddidiya - Muhammad Qasim; Prof Dr. Matloob Ahmad (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Mujaddidi Sofia examined the flaws in his own era and then tried his best to rectify them. The first cause of these evils was the flight of people and properties from the Shariah. Which had paved the way for the thoughts and ideas of Aghyar and had settled in the veins of the Muslims. The second most important reason was that some so-called sophists and Sofia Kham considered Shariah to be separate from Tareeqah. Once this is achieved, then there is no need for Shariah. These reasons destroyed the foundations of Islamic Shariah at the hands of the Muslims themselves and such people were born in the Sufi class. Those who did not believe in prayer, nor in hell, nor in heaven, nor in the resurrection. Below is an overview of Mujaddidi Sofia's reforming works to make it clear that he somehow implemented the Shari'a by creating an intellectual and practical revolution in his own era.